2015
DOI: 10.5539/gjhs.v7n2p351
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Students’ Views of Nursing Education Quality: A Qualitative Study

Abstract: Background:Nursing education is currently facing challenges related to the application of nursing knowledge in clinical environments and inability of students in application of nursing procedures in clinical settings. Nursing students themselves represent the best means of identifying these challenges. This study was conducted aimed to understand the nursing students’ viewpoints and experiences concerning the challenges and deficiencies of the nursing education system.Methods:This qualitative study that has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 15 publications
3
44
1
4
Order By: Relevance
“…They undoubtedly deemed more relevant and useful those they could see as clearly connected with the day-to-day nursing work and those that required practical skills and techniques; these results match those of Fuentes-Pumarola et al [20]. Kermansaravi et al [32] found that students liked theoretical contents that had applied value; otherwise studying them was a waste of time. We can state that there was a preference for biomedical courses, which could contrast/contradict the long struggle of nursing to carry out the conceptual and theoretical framework change in nursing training, as opposed to the traditional biomedical model [35].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…They undoubtedly deemed more relevant and useful those they could see as clearly connected with the day-to-day nursing work and those that required practical skills and techniques; these results match those of Fuentes-Pumarola et al [20]. Kermansaravi et al [32] found that students liked theoretical contents that had applied value; otherwise studying them was a waste of time. We can state that there was a preference for biomedical courses, which could contrast/contradict the long struggle of nursing to carry out the conceptual and theoretical framework change in nursing training, as opposed to the traditional biomedical model [35].…”
Section: Discussionsupporting
confidence: 69%
“…The interviewees were disappointed in seeing nursing staff who did not provide care based on the latest scientific evidence, as they learned in university. Several authors found differences between what students learned at university and what they later saw in the healthcare settings [9,14,20,31,32]. The literature also suggests that idealized care and actual care act like two opposing forces that graduates try to counterbalance [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Poor educational planning, wasting the time of students in the clinical education and inadequate preparation of educators and students in clinical education was another undesirable experience of nursing students from clinical education in nursing. Kermansaravi et al (17) in their study, showed that the job description of the students in some sections are not clear and the educational planning is not in a desirable condition. Some of the participating students in the study stated that the undesirable planning of their apprenticeship and clinical education wastes their time in the clinical education environment.…”
Section: Discussionmentioning
confidence: 97%
“…Considering the special nature of nursing profession, it is necessary for the learners of this profession to have a real understanding of material content so that they are competent in specific clinical situations to use their learnings; using active educational methods is significantly effective in increasing deep thinking skills and stability of materials in the students' minds. 13 Participatory education has the best effect on the change in nurses' performance [14][15][16] also, learning in the workplace, which can be formal and informal, is one of the most powerful training methods; also, the workplace is one of the most appropriate teaching and learning settings. 17 However, the education staff is a very strategical and important issue as the foundation for the development of any organization, which contributes to the dynamics of the organization.…”
Section: Discussionmentioning
confidence: 99%